Waste Management Technology - Rathakrishnan, L (Ushus Journal of Business Management, 2021)
As the population grows there is an increase in wastage from our economic activities. Causing pollution on land, water, air, and on all other living things. India, being the second largest populous country in the world produces enormous organic and inorganic waste. While the household and agriculture waste may be used immediately after simple treatment, the waste generated from industries cannot be used as it is. If the industrial leftovers are effectively recycled or retreated by adopting suitable management techniques, then there will be no unwanted element in the environment. Rather, all nutrient elements if recycled, may enrich soil and other natural resources. Scientists and economists have found new technology to treat all waste as a source through recycling, conversion, source of energy, and land reclamation. Now, they have come to the conclusion that waste is a waste if untreated, but if it is modified in some other form, it is a potential resource and a wealth for our future. However, the only requirement is that it should be treated properly or taken care of. This paper examines some of the technology adopted by scientists, economists to use the waste as one of the potential resource either through knowledge or any other means for increasing productivity, maximising returns, and reducing pile up of unused waste. Successful case studies have been reviewed and analysed critically.